TUAN GURU'S SPIRITUAL LEADERSHIP AND CONFLICT OF RELIGIOUS IDEOLOGY IN LOMBOK - Pardi, M. Habib Husnial; Said, Muhammad (JOURNAL OF INDONESIAN ISLAM, 2026)
This article examines the role of Tuan Guru as a pesantren leader in resolving religious ideological conflicts between the Ahl al-Sunnah wa al-Jamaah–Nahdlatul Wathan and Sunnah communities in East Lombok through a spiritual leadership model. Using a qualitative case study supported by phenomenological and ethnographic approaches, the study investigates the dynamics of religious ideological conflict and the implementation of spiritual leadership in conflict resolution. The findings reveal that differences in religious ideology constitute the primary source of conflict, often triggering broader social tensions. Tuan Guru’s spiritual leadership effectively fosters reconciliation by promoting dialogue, mutual understanding, and harmonious social relations despite enduring ideological differences. This study offers a comprehensive perspective on religious conflict by integrating spiritual guidance, community leadership, and contemporary conflict resolution approaches. It contributes to the theoretical development of spiritual leadership and provides practical insights for education policymakers, community leaders, and scholars concerned with conflict management in Islamic societies.